(untitled) (London Journal of Medical and Health Research, 2024)
Background: Diabetes mellitus (DM) has a global prevalence of 536.6 million people, which an estimated rise of 12.2% by 2045. Diabetes management is expensive, hence alternate management options are being explored. The World Health Organization recognizes some plants and plant-based meals as excellent diabetes treatment agents. These include cocoyam (CYN), soya bean (SB), and Bambara groundnut (BGN). The purpose of this study was to evaluate these extracts’ hypoglycemic, weight changes and histological effects. Methodology: CYN, SB, and BGN were sourced and processed to generate high-quality flour, which were pelletized and oven-dried at 60C, before storage. The eighty-two male albino rats weighing between 134 and 247 g, were administered with low-dose fructose to induce insulin resistance. Type 2 diabetes mellitus (T2DM) was induced with intraperitoneal injection of streptozotocin, following which a 28 days intervention formulations were administered. Throughout the investigation, the weights of the rats were recorded while on the 28th day, their organs and blood samples were collected from killed rats for histological examination and blood glucose analysis respectively. Results & Discussion: The investigation revealed an average random blood glucose (RBG) levels that varied significantly over time for each group, displaying a consistent pattern of changes across the entire group from week 1 to week 4 (F=79.106, p<0.01) (F=76.755, p<0.001), with significant differences between groups (F= 13.963, p<0.001). Group A diabetic rats exceeded the normal control group in terms of anti-diabetic efficacy, rat body weight gain of 8.85% over four weeks period, an increase in liver weight in the intervention formulation groups and an unchanged pancreatic weight. Histological examinations revealed varied levels of tissue regeneration and intra-hepatic inflammation in pancreatic and hepatic cells between groups treated with different intervention formulations. Conclusion: Group A rats, treated with formulation 1 (16.6% CY+16.6%SB+16.6%BGN) had histological characteristics identical to the normal control group, exceeding the standard control groups. This showed that these formulations successfully stopped STZ-induced organ damage and resulted in successful organ healing. Furthermore, the Cocoyam-Soya bean-Bambara groundnut flour blend demonstrated hypoglycemic, tissue regeneration, and hepato-pancreatic protective effects in STZ-induced diabetic rats, showing its potential as a therapeutic supplement in the treatment of diabetes mellitus.